A Comprehensive Study on Mathematical Sampling before Testing For COVID-19 Infected Candidates - Srivastav, Manoj Kumar; Nath, Asoke (International Journal of Computer Sciences and Engineering, 2020)
COVID-19 is a new infectious viral disease and it is great challenge to the entire globe. The corona virus COVID-19 is declared as pandemic and it will change the life style of human in our society. The number of infection cases related to COVID-19 is increasing almost exponentially like any other pandemic disease. Till date there is no vaccine or medicine which can prevent from infection of COVID-19. To combat infection from COVID-19 the Governments are trying to reduce the spread of the virus by doing some standard techniques such as lockdown and then testing, tracing, social distancing, quarantining and isolation of citizens. In the present paper the authors have tried to introduce explore the reference sampling to isolate COVID-19 infected patients. Reference sampling will be helpful to collect data and give a proper idea to testing for covid-19 patient.